EFFECTS OF PARATIC FACTORS ON MEAT PRODUCTIVITY OF KARAKALPAK SUR KARAKUL RAM - Bobokulov Nasillo Asadovich; Urimbetov Ahmet Abdirazakovich (European Journal of Agricultural and Rural Education, 2022)
The meat productivity of sheep of various etiologic types is examined in this article, as well as the study of the etiologic characteristics of the Karakalpak sur, Karakul rams; based on the study of the influence of these characteristics on the formation and manifestation of productivity in rams and their offspring, it is necessary to determine ways to improve their productivity.